Concordance of an in-house 2-steps PCR-SSP and nanopore sequencing for HLA-B*57:01 and HLA-B*58:01 typing: a comparative study - Intharuangrung, Nattapong; Sirikul, Chonticha; Nimsamer, Pattaraporn; Wongsurawat, Thidathip; Saejia, Auttachai; Anukul, Nampeung (Frontiers in Genetics, 2025)
This study reports an optimized in-house 2-step PCR-SSP assay for rapid, cost-effective detection of HLA-B*57:01 and HLA-B*58:01 in routine pharmacogenomics laboratory. This assay employs allele-specific primers positioned within exon 2–3 boundaries, validated in silico against common HLA-B alleles. Using 30 clinical DNA samples, our PCR workflow (<1 h) showed 100% concordance at 2-field resolution with Oxford Nanopore sequencing performed using ligation-based sequencing kit with PCR barcoding. Cohen’s kappa was 1.00 with 95% CI. The turnaround time and reagent cost per sample were reduced to 1 h of hands-on PCR time and USD 7 per sample, respectively. These do not include DNA extraction or gel electrophoresis analysis. This 2-step PCR-SSP offers a robust alternative for pharmacogenomic screening in resource-limited settings for detecting the HLA-B*57:01 and HLA-B*58:01.